Supporting Students’ Basic Science Process Skills by Augmented Reality Learning Media - Tiara Lestari Paembonan; Jaslin Ikhsan (Journal of Educational Science and Technology (EST), 2021)
Science process skills (SPS) are one of the skills needed in the chemistry learning process, in order to gain a complete understanding of the concepts. This skills categorized into two types; basic and integrated. This research aimed to develop a product of Augmented Reality (AR) learning media then to know its feasibility, practicality, and effectiveness on students’ basic SPS on acid base learning. The research adopted Research and Development (R&D) with 4-D model consisted of define, design, develop, and disseminate stages. Questionnaire was used to measure the feasibility and practicality. Then, the obtained data were analyzed by qualitative and quantitative descriptive. In addition, SPS test was used to measure the effectiveness of AR learning media and the data were analyzed by the test of One-way ANOVA, Tukey’s Post Hoc test, and General Linear Model (GLM) Univariate. The result showed that the AR learning media is feasible, practical, and effective with big influence to support students’ basic SPS on acid base learning.